Pengaruh Fenomena Fisika Lingkungan Terhadap Kehidupan dan Ekosistem Lokal di Gampong Kopelma Darussalam: Sebuah Tindakan Edukasi dan Penyadaran - Mustika, Cut Riski (Intelektualita, 2024)
This study investigates the impact of environmental physics phenomena on Gampong Kopelma Darussalam, including climate change, renewable energy usage, waste management, pollution, natural resource conservation, and community education. Gampong Kopelma Darussalam, rich in natural beauty and resources, faces challenges due to climate change, environmental shifts, and human activities. Climate change, such as rising temperatures and irregular rainfall, affects agriculture and livelihoods. Mitigation and adaptation efforts are needed. The use of renewable energy, particularly solar drying of clothes, reduces energy consumption and promotes sustainability. Issues like cigarette smoke, vehicle emissions, and waste management pose health and environmental problems. Community education is crucial. The conversion of natural resources, like farmland, impacts food security. Community education on conservation is vital for environmental balance. Collaboration between the government, community, and stakeholders is key to protecting the environment. Sustainable practices like renewable energy and improved waste management can create a cleaner, healthier, and more sustainable environment in Gampong Kopelma Darussalam while preserving its natural heritage